2017
DOI: 10.1016/j.aller.2016.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphisms of IL-2 , but not IL-12 and IFN - γ , are associated with increased susceptibility to chronic spontaneous urticaria

Abstract: SNP at position -330 and +166 of IL-2 gene are differently expressed in CSU. The haplotype GT of IL-2 at -330 and +166 might confer vulnerability to a number of immunological disorders in Iranian region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…NK2 cells are capable of producing many important cytokines, including IL-4, IL-5, and IL-13, which further aggravates the pathology of CSU ( 188 ). Consistent with this, decreased levels of IFN-γ in serum of patients with CSU suggest that NK1 cells are not dominant compared with NK2 cells ( 189 ).…”
Section: The Crosstalk Of Immune Cells In Csusupporting
confidence: 54%
“…NK2 cells are capable of producing many important cytokines, including IL-4, IL-5, and IL-13, which further aggravates the pathology of CSU ( 188 ). Consistent with this, decreased levels of IFN-γ in serum of patients with CSU suggest that NK1 cells are not dominant compared with NK2 cells ( 189 ).…”
Section: The Crosstalk Of Immune Cells In Csusupporting
confidence: 54%
“…No report of the association between IL-2 + 166 polymorphism and IBD currently exists in the literature. Meanwhile previous studies from Iran demonstrated that the IL-2 (-330, +160) GT haplotype is more common in people with irritable bowel syndrome [29], chronic spontaneous urticaria [61], juvenile systemic lupus erythematosus [55], and juvenile idiopathic arthritis [56]. The present study indicated that the IL-2 -330 GG genotype is associated with both CD and UC, whereas the GT genotype of this SNP is protective toward CD in Iranian patients.…”
Section: Discussionmentioning
confidence: 50%
“…4 Polymorphism of IL2 -330T/G might also affect transcription and translation of the IL-2 gene through activation of the transcription factor. 5 Recently, it was estimated that IL-2 polymorphisms are related to susceptibility to several diseases, such as chronic spontaneous urticaria 6 and Graves' disease. 7 However, there are conflicting results regarding the impact of IL2 -330T/G polymorphism on the risk of pulmonary TB.…”
Section: Introductionmentioning
confidence: 99%